Simone Weil: The Mystical Ascetic - Nagy, Endre (European Journal of Mental Health, 2010)
The essay deals with the life and work of the great but contested figure of Catholicism of the last century, Simone Weil. It follows up the career of her life from the intellectual illumination (mystical visions) through her destiny event (submerged in the ‘sub-world’) up till her resistance to being baptised. It looks at her teachings together with Max Weber’s theory on modernisation, that is, the ‘Ausdifferenzierungen’ of various spheres of life (economy, politics, etc.), that excludes the possibility of life and of the ethics of brotherliness in the 20th century. The essay seeks to point out the life and work of Simone Weil as a whole but disapproves of this tenet. For she has found in everyday life holiness and sacrilege at the same time, from which God is revealed. The essay deals with the question why she resisted being baptised emphasising that the main reason was her keeeping aloof of the Old Testament and that in her view the Church showed totalitarian traits throughout its history.